RadioPharmaDose, a java-based open-source software for estimating and reporting internal radiation doses. Issue 1 (6th June 2018) - Bakkali, Jaafar EL; Mansouri, Hamid; Doudouh, Abderrahim
Abstract : In this work, a user-friendly Java-based open-source software has been developed for internal radiation dosimetry. Based on values published by the International Commission on Radiological Protection (ICRP), the software calculates the estimated absorbed dose for each organ and also the estimated effective dose, this for about forty of the most known radioactive drugs. In addition, the present software offers many features which include: 1) a very friendly graphical user-interface (GUI) designed to facilitate the process of selecting mandatory input data such as radiopharmaceutical product, administered activity and patient's data, 2) a tool for generating a medical report, which can be exported as PDF file or printed directly and then incorporated into the patient's record, 3) a SQLite database for storing patient's specific and dosimetric data. We believe that the present software can be a useful tool for nuclear medicine workers. It is freely available for download on GitHub (https://github.com/EL-Bakkali-Jaafar/RadioPharmaDose ).